Analisis Sistem Informasi Akuntansi Pembayaran Biaya Tagihan Pemakaian Air Bersih pada Perusahaan PDAM Tirtanadi Kota Medan - Faujiah Faujiah; Nurlaila Nurlaila (Universitas Muhammadiyah Enrekang, 2022)
The purpose of this study is to find out how the accounting information system works to receive bills made at PDAM Tirtandi. The method used in this study uses a qualitative descriptive research method data collection through observation and documentation. Based on the results of this studyIt is determined that the billing information system accepts bills for water consumption. Cleanliness of PDAM Tirtandi Medan City is considered good because the system is cleanis clear and structured. However, the company still has problems with the accounting information system when receiving invoice payments. These restrictions include B. Invoices received in the accounting information system, there are customers who are late. In addition, the billing information system is network dependent. It can also cause network errors which can interfere with the operation of the system with the PDAM. PDAM tries to collect arrears from customers who have not paid and if payment has not been made for more than 3 months, PDAM Tirtandi will cut off the customer's water supply.